1999
DOI: 10.1046/j.1365-2141.1999.01399.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis and bleeding in myeloproliferative disorders: identification of at‐risk patients with whole blood platelet aggregation studies

Abstract: Summary.Seventy-five patients with chronic myeloproliferative disorders were studied to investigate platelet function by simultaneous measurement of platelet aggregation by the impedance method and ATP dense granule release using a whole blood platelet lumi-aggregometer, in an attempt to identify patients at risk for thrombosis and bleeding.Thirty-nine patients had at least one abnormal result indicating platelet hyperactivity (i.e. impedance or release with one agonist being above the reference range); 16 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 33 publications
4
30
1
Order By: Relevance
“…The ability of compounds to induce aggregation was determined by measuring the impedance (Ohms) of the whole blood which is directly proportional to the aggregatory response. 20 As expected, collagen alone elicited a robust response at all the time points illustrating the stability of the platelets over the course of the study. The ability of the platelets to form aggregates was confirmed both before and after the course of the study by the addition of collagen ( Figure 3c; PRE and POST conditions).…”
Section: Resultssupporting
confidence: 70%
“…The ability of compounds to induce aggregation was determined by measuring the impedance (Ohms) of the whole blood which is directly proportional to the aggregatory response. 20 As expected, collagen alone elicited a robust response at all the time points illustrating the stability of the platelets over the course of the study. The ability of the platelets to form aggregates was confirmed both before and after the course of the study by the addition of collagen ( Figure 3c; PRE and POST conditions).…”
Section: Resultssupporting
confidence: 70%
“…The thrombohaemorrhagic complications occurring in MPD incited many authors to investigate the function of platelets and to correlate the detected abnormalities with these clinical aspects and with changes of bleeding time [3,4,[23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The bleeding tendency may in part be related to an acquired von Willebrand factor (VWF) deficiency associated with consumption of high molecular weight VWF multimers, abnormalities in platelet membrane glycoprotein (GP) and agonist receptor contents and defective agonistmediated platelet aggregation (Kaywin et al, 1978;Mazzucato et al, 1989;Balduini et al, 1991;van Genderen et al, 1997). Likewise, a propensity for thrombosis might be multifactually explained by a variety of abnormalities, implying increased platelet activation such as abnormal eicosanoid metabolism, increased granule secretion as assessed by serological measurement of alpha-granule products and spontaneous platelet aggregation (Cortelazzo et al, 1981;Landolfi et al, 1992;van Genderen et al, 1999;Manoharan et al, 1999). Furthermore, coagulation studies have revealed increased markers of the activated coagulation system and abnormal levels of the natural anticoagulants antithrombin, protein C and protein S in a proportion of patients (Falanga et al, 1994;Bucalossi et al, 1996).…”
mentioning
confidence: 99%
“…Recently, Manoharan et al (1999) demonstrated a correlation between agonist-induced platelet hyperactivation and a history of thrombosis, using whole blood aggregometry, thus omitting the potential artefacts associated with platelet centrifugation.…”
mentioning
confidence: 99%